Early childhood intervention for the poor: Long term outcomes - Alison Andrew; Orazio P. Attanasio; Britta Augsburg; Lina Cardona-Sosa; Monimalika Day; Michele Giannola; Sally Grantham-McGregor; Pamela Jervis; Costas Meghir; Marta Rubio Codina (Yale University, Economic Growth Center, 2024)
Early childhood interventions aim to promote skill acquisition and poverty reduction. While their short-term success is well established, research on longer-term effectiveness is scarce, particularly in LDCs. We present results of a randomized scalable intervention in India, that affected developmental outcomes in the short-term, including cognition (0.36 SD p=0.005), receptive language (0.26 SD p=0.03) and expressive language (0.21 SD p=0.03). After 4.5 years, when the children were on average 7.5 years old, IQ was no longer affected, but impacts persisted relative to the control group in numeracy (0.330 SD, p=0.007) and literacy (0.272 SD, p=0.064) driven by the most disadvantaged.
Keywords: O12; 330; Early Childhood Development; Stimulation Programs; Scaling up